Cerebellar Processing Common to Delay and Trace Eyelid Conditioning - Halverson, Hunter E. (J Neurosci, 2018)
Results from previous lesion studies have been interpreted as evidence that the cerebellar cortex plays different roles for delay and trace conditioning of eyelid responses. However, the cerebellar cortex is organized by parasagittal stripes of Purkinje cells (PCs) that converge onto common deep nucleus neurons and receive common or related climbing fiber inputs. Based on this organization, we hypothesized that cerebellar tasks involving the same response system, such as delay and trace eyelid conditioning, would engage the same PCs and that the relationships between PC activity and expression of behavioral responses would be similar for both tasks. To test these hypotheses, we used tetrode recordings from eyelid PCs in rabbits during expression of delay- and trace-conditioned eyelid responses. Previous recording studies during delay conditioning described a strong relationship between eyelid PC activity and the kinematics of conditioned eyelid responses. The present results replicate these findings for delay conditioning and show that the same relationship exists during trace eyelid conditioning. During transitions from delay to trace responding, the relationship between eyelid PCs and behavioral responses was relatively stable. We found that an inverse firing rate model tuned to predict PC activity during one training paradigm could then predict equally well the PC activity during the other training paradigm. These results provide strong evidence that cerebellar cortex processing is similar for delay and trace eyelid conditioning and that the parasagittal organization of the cerebellum, not the conditioning paradigm, dictate which neurons are engaged to produce adaptively timed conditioned responses. SIGNIFICANCE STATEMENT A variety of evidence from eyelid conditioning and other cerebellar-dependent behaviors indicates that the cerebellar cortex is necessary for learning and proper timing of cerebellar learned responses. Debates exist about whether trace eyelid conditioning data show that fundamentally different mechanisms operate in the cerebellum during tasks when input from the forebrain is necessary for learning. We show here that learning-related changes in a specific population of Purkinje cells control the timing and amplitude of cerebellar responses the same way regardless of the inputs necessary to learn the task. Our results indicate the parasagittal organization of the cerebellar cortex, not the complexity of inputs to the cerebellum, determines which neurons are engaged in the learning and execution of cerebellar-mediated responses.